Avaliação dos principais critérios de desempenho de terceirização de tecnologia da informação para a gestão contratual em empresas públicas - Felisoni, Paulo Ribeiro (2020)
Although Information Technology Outsourcing (ITO) is common place in private companies, it is less common in public organizations. In addition, extant literature focuses mainly on private companies and researchers from public organizations use and replicate these results often without adequate validation for the public context. This points to a scenario in which ITO studies may have worse results due to the lack of an appropriate theoretical framework. To analyze this disparity, the existing literature on IT, public organizations and outsourcing is reviewed. A systematic review of the literature allows to extract the content organized by groups. Thus, a framework is proposed to understand the main dimensions of monitoring IT outsourcing for public organizations. The results point to four main criteria (monitoring, relationship, performance and uncertainty) subdivided into 16 sub-criteria, validated, classified and hierarchized using the Fuzzy-AHP (Fuzzy Analytic Hierarchy Process) method. This study contributes to the literature by refining the IT outsourcing theories for the public sector and providing a platform for advances in future studies. In addition, it also contributes to the discussion on three different hierarchical views according to the strategic, tactical and operational profiles, emerging from different views and concerns regarding the management and inspection of IT outsourcing contracts in public companies.